DESKRIPSI KARAKTER DALAM “ ANAK SEJUTA BINTANG” KARYA AKMAL NASERY BASRAL DAN IMPLIKASINYA TERHADAP PEMBELAJARAN SASTRA D SMA - M. Rais Salim (EDUKASI, 2018)
The objective of this research to describes character of  loving god,  the character of procet them selves, ? the character of  helping each other, describes the character of  loving nation  in a million stars of child. This research is used qualitative approached with content technique. Based on the descriptions above, it can be concluded that the character of a million stras of child by Akmal Nasery Basral  is very important to use ase educating children, so that it will be in their selves, the character  of loving god, becoming  an independent, helping each other, character of loving invironmental and character of loving the nation. Based on the result, it is suggested that the implementation of educational character seriously, professionals, and maximally paid attention. And  it also hoped to be implemented as source of learning character to the senior high school students.Key word: A Million Stars od Child